<h2><u>1. Determining the value of x and y:</u></h2>
Given equation(s):
To determine the point of intersection given by the two equations, it is required to know the x-value and the y-value of both equations. We can solve for the x and y variables through two methods.
<h3 /><h3><u>Method-1: Substitution method</u></h3>
Given value of the y-variable: 3x - 1
Substitute the given value of the y-variable into the second equation to determine the value of the x-variable.
![\implies 3x + y = -7](https://tex.z-dn.net/?f=%5Cimplies%203x%20%2B%20y%20%3D%20-7)
![\implies3x + (3x - 1) = -7](https://tex.z-dn.net/?f=%5Cimplies3x%20%2B%20%283x%20-%201%29%20%3D%20-7)
![\implies3x + 3x - 1 = -7](https://tex.z-dn.net/?f=%5Cimplies3x%20%2B%203x%20-%201%20%3D%20-7)
Combine like terms as needed;
![\implies 3x + 3x - 1 = -7](https://tex.z-dn.net/?f=%5Cimplies%203x%20%2B%203x%20-%201%20%3D%20-7)
![\implies 6x - 1 = -7](https://tex.z-dn.net/?f=%5Cimplies%206x%20-%201%20%3D%20-7)
Add 1 to both sides of the equation;
![\implies 6x - 1 + 1 = -7 + 1](https://tex.z-dn.net/?f=%5Cimplies%206x%20-%201%20%2B%201%20%3D%20-7%20%2B%201)
![\implies 6x = -6](https://tex.z-dn.net/?f=%5Cimplies%206x%20%3D%20-6)
Divide 6 to both sides of the equation;
![\implies \dfrac{6x}{6} = \dfrac{-6}{6}](https://tex.z-dn.net/?f=%5Cimplies%20%5Cdfrac%7B6x%7D%7B6%7D%20%20%3D%20%5Cdfrac%7B-6%7D%7B6%7D)
![\implies x = -1](https://tex.z-dn.net/?f=%5Cimplies%20x%20%3D%20-1)
Now, substitute the value of the x-variable into the expression that is equivalent to the y-variable.
![\implies y = 3(-1) - 1](https://tex.z-dn.net/?f=%5Cimplies%20y%20%3D%203%28-1%29%20-%201)
![\ \ = -3 - 1](https://tex.z-dn.net/?f=%5C%20%5C%20%3D%20-3%20-%201)
![= -4](https://tex.z-dn.net/?f=%3D%20-4)
Therefore, the value(s) of the x-variable and the y-variable are;
![\boxed{y = -4}](https://tex.z-dn.net/?f=%5Cboxed%7By%20%3D%20-4%7D)
<h3 /><h3><u>Method 2: System of equations</u></h3>
Convert the equations into slope intercept form;
![\implies\left \{ {{y = 3x - 1} \atop {3x + y = -7}} \right.](https://tex.z-dn.net/?f=%5Cimplies%5Cleft%20%5C%7B%20%7B%7By%20%3D%203x%20-%201%7D%20%5Catop%20%7B3x%20%2B%20y%20%3D%20-7%7D%7D%20%5Cright.)
![\implies \left \{ {{y = 3x - 1} \atop {y = -3x - 7}} \right.](https://tex.z-dn.net/?f=%5Cimplies%20%5Cleft%20%5C%7B%20%7B%7By%20%3D%203x%20-%201%7D%20%5Catop%20%7By%20%3D%20-3x%20-%207%7D%7D%20%5Cright.)
Clearly, we can see that "y" is isolated in both equations. Therefore, we can subtract the second equation from the first equation.
![\implies \left \{ {{y = 3x - 1 } \atop {- (y = -3x - 7)}} \right.](https://tex.z-dn.net/?f=%5Cimplies%20%5Cleft%20%5C%7B%20%7B%7By%20%3D%203x%20-%201%20%7D%20%5Catop%20%7B-%20%28y%20%3D%20-3x%20-%207%29%7D%7D%20%5Cright.)
![\implies \left \{ {{y = 3x - 1} \atop {-y = 3x + 7}} \right.](https://tex.z-dn.net/?f=%5Cimplies%20%5Cleft%20%5C%7B%20%7B%7By%20%3D%203x%20-%201%7D%20%5Catop%20%7B-y%20%3D%203x%20%2B%207%7D%7D%20%5Cright.)
Now, we can cancel the "y-variable" as y - y is 0 and combine the equations into one equation by adding 3x to 3x and 7 to -1.
![\implies\left \{ {{y = 3x - 1} \atop {-y = 3x + 7}} \right.](https://tex.z-dn.net/?f=%5Cimplies%5Cleft%20%5C%7B%20%7B%7By%20%3D%203x%20-%201%7D%20%5Catop%20%7B-y%20%3D%203x%20%2B%207%7D%7D%20%5Cright.)
![\implies 0 = (6x) + (6)](https://tex.z-dn.net/?f=%5Cimplies%200%20%3D%20%286x%29%20%2B%20%286%29)
![\implies0 = 6x + 6](https://tex.z-dn.net/?f=%5Cimplies0%20%3D%206x%20%2B%206)
This problem is now an algebraic problem. Isolate "x" to determine its value.
![\implies 0 - 6 = 6x + 6 - 6](https://tex.z-dn.net/?f=%5Cimplies%200%20-%206%20%3D%206x%20%2B%206%20-%206)
![\implies -6 = 6x](https://tex.z-dn.net/?f=%5Cimplies%20-6%20%3D%206x)
![\implies -1 = x](https://tex.z-dn.net/?f=%5Cimplies%20-1%20%3D%20x)
Like done in method 1, substitute the value of x into the first equation to determine the value of y.
![\implies y = 3(-1) - 1](https://tex.z-dn.net/?f=%5Cimplies%20y%20%3D%203%28-1%29%20-%201)
![\implies y = -3 - 1](https://tex.z-dn.net/?f=%5Cimplies%20y%20%3D%20-3%20-%201)
![\implies y = -4](https://tex.z-dn.net/?f=%5Cimplies%20y%20%3D%20-4)
Therefore, the value(s) of the x-variable and the y-variable are;
![\boxed{y = -4}](https://tex.z-dn.net/?f=%5Cboxed%7By%20%3D%20-4%7D)
<h2><u>2. Determining the intersection point;</u></h2>
The point on a coordinate plane is expressed as (x, y). Simply substitute the values of x and y to determine the intersection point given by the equations.
⇒ (x, y) ⇒ (-1, -4)
Therefore, the point of intersection is (-1, -4).
<h3>Graph:</h3>